The role of preoperative systemic treatment in patients with breast cancer - Dębska-Szmich, Sylwia; Krakowska, Magdalena; Czernek, Urszula; Habib-Lisik, Maja; Zięba, Agnieszka; Potemski, Piotr (Contemporary Oncology/Współczesna Onkologia, 2016)
The goal of preoperative pharmacotherapy in patients with breast cancer is to enable breast conserving surgery in stage T3N0-1M0 or radical mastectomy in patients with primary inoperative tumors (T1-4N0-3M0). The choice of optimal treatment should be based not only on risk factors resulting from the stage but also on predicted cancer responsiveness to the treatment. The breast cancer subtypes defined by immunohistochemical profile (expression of ER, PR, HER2 and Ki67) are characterized by different responsiveness to therapy. Complete response confirmed by histopathological evaluation after neoadjuvant chemotherapy is a positive prognostic factor in some breast cancer subtypes. This marker is not of value in postmenopausal patients with ER/PR+ HER2– tumors, who are candidates for neoadjuvant hormone therapy. These patients have a good prognosis if in a histopathological report after surgery there are features such as pT1, pN0, Ki67 < 3%, and ER Allred score ≥ 3. The goal of the paper is to present current knowledge about preoperative pharmacotherapy of breast cancer.